2015
DOI: 10.1016/j.cell.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Code for Identity in the Vomeronasal System

Abstract: SUMMARY In social interactions among mammals, individuals are recognized by olfactory cues, but identifying the key signals among thousands of compounds remains a major challenge. To address this need, we developed a new technique, Component-Activity Matching (CAM), to select candidate ligands that “explain” patterns of bioactivity across diverse complex mixtures. Using mouse urine from eight different sexes and strains, we identified 23 components to explain firing rates in seven of eight functional classes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 37 publications
0
57
0
Order By: Relevance
“…In mice, a handful of monomolecular chemical cues have been identified that play important roles in VNO pheromonal responses (Chamero et al, 2007; Haga et al, 2010; Ferrero et al, 2013; Fu et al, 2015). However, with the exception of major urinary proteins promoting territorial marking by males (Kaur et al, 2014), live animals are in many cases necessary to trigger pheromonal actions, thus leaving intact the contribution of multiple sensory cues in triggering behavior output.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, a handful of monomolecular chemical cues have been identified that play important roles in VNO pheromonal responses (Chamero et al, 2007; Haga et al, 2010; Ferrero et al, 2013; Fu et al, 2015). However, with the exception of major urinary proteins promoting territorial marking by males (Kaur et al, 2014), live animals are in many cases necessary to trigger pheromonal actions, thus leaving intact the contribution of multiple sensory cues in triggering behavior output.…”
Section: Discussionmentioning
confidence: 99%
“…Although combining simple stimulus-features from sensory organs for higher cognition were often postulated and reported (Buck and Axel, 1991; Yeshurun and Sobel, 2010; Fu et al, 2015), findings of some cells in a given site which responded to multiple stimuli (as the literature intermittently described in bits and pieces) have reinforced the popular but undue impression that somehow convergence and combination occurred but in a stochastic and random fashion. Obviously, such sporadic combinations can easily take place in various ways without conforming to the power-of-two based permutation logic.…”
Section: Discussionmentioning
confidence: 99%
“…Some pheromones are derived by direct chemical transformation of internal state-regulating hormones into externally broadcast pheromones. Circulating steroid and internal state hormones such as testosterone, estradiol, and pregnanolone can be directly transformed into externally emitted chemosensory ligands [27]. Some steroids are sulfated to promote excretion into the environment.…”
Section: Pheromone Production Varies With Internal Statementioning
confidence: 99%
“…Some steroids are sulfated to promote excretion into the environment. Once emitted, sulfated steroids potently activate VNO sensory neurons of receiving individuals and serve as faithful indicators of the emitter’s internal state [27,28,31,32]. For example, one sulfated estrogen is emitted by ovulating females as a byproduct of the reproductive cycle, and then functions secondarily as part of a pheromone blend that promotes male courtship behavior [28].…”
Section: Pheromone Production Varies With Internal Statementioning
confidence: 99%